Numerical simulation of plateau formation by an electron bunch on the distribution of an accelerating wakefield in a plasma - Maslov, V.I.; Ovsiannikov, R.T.; Delerue, N.; Kubytskyi, V.; Levchuk, I.P.; Onishchenko, I.N. (Вопросы атомной науки и техники, 2020)
Over the past decade the production of multi-gigaelectrons from laser-driven and electron-bunch-driven plasma accelerators has been successfully demonstrated. However, applications require improvements of accelerated bunch size and its energy spread. One promising candidate to satisfy these requirements is to externally inject an electron bunch into an electron-bunch-driven plasma accelerator. We present studies on the optimization of the self-consistent distribution of an accelerating wakefield of plateau type, which can lead to improvement of final quality of the externally injected and accelerated electron bunch, using simulations with the particle-in-cell code LCODE. We quantified the effect of the injected bunch density on the plateau formation in the blowout regime. За останнє десятиліття було успішно продемонстровано отримання електронів з енергією декілька гігаелектронвольт у плазмових прискорювачах з лазерним імпульсом і електронним згустком. Однак застосування вимагають поліпшення розміру згустку, що прискорюється, і його енергетичного розкиду. Одним з перспективних кандидатів для задоволення цих вимог є інжекція електронного згустку ззовні в плазмовий прискорювач, керований електронним згустком. Ми представляємо дослідження з оптимізації самоузгодженого розподілу прискорюючого кільватерного поля типу плато, яке може привести до поліпшення кінцевої якості зовні інжектованого і прискореного електронного згустку, з використанням моделювання за допомогою PIC-коду LCODE. Ми кількісно оцінили вплив щільності інжектованого згустку на формування плато в нелінійному режимі перекидання. За последнее десятилетие было успешно продемонстрировано получение электронов с энергией несколько гигаэлектронвольт в плазменных ускорителях с лазерным импульсом и электронным сгустком. Однако приложения требуют улучшения размера ускоряемого сгустка и его энергетического разброса. Одним из многообещающих кандидатов для удовлетворения этих требований является инжекция электронного сгустка извне в плазменный ускоритель, управляемый электронным сгустком. Мы представляем исследования по оптимизации самосогласованного распределения ускоряющего кильватерного поля типа плато, которое может привести к улучшению конечного качества внешне инжектируемого и ускоренного электронного сгустка, с использованием моделирования при помощи PIC-кода LCODE. Мы количественно оценили влияние плотности инжектированного сгустка на формирование плато в нелинейном режиме опрокидывания.